Límite de funciones reales con apoyo de GeoGebra - Medina García, Nélida Salomé (2021)
The objectives of this workshop are: 1). Train participants in the handling of Input Bar, Views, Spreadsheet, Options menu, Slider, Text, Scroll graphical view, Intersection, Perpendicular and some commands of the GeoGebra Classic 5 program; 2). Facilitate significant learning of the formal concept of limit of a real function at a number and at infinity and, 3). Develop the ability to communicate and represent mathematical ideaswith limit of real functions. Development: We explore the GeoGebra Views, tools and commands that we will use. We present an Activity that contains the intuitive and formal definitions of limit of a real function at a number and at infinity, examples on limit of functions to solve and questions oriented to the intuitive concept and later to a dynamic construction of the formal concept of limit, with GeoGebra support. We proceed in a similar way with the concept limit of a real function at infinity. We end the activity with an example that will be solved by the participants in small groups. Expected results. The use of GeoGebra will allow the participant to increase the number of examples that can be observed and generate certainties on the topic limit of functions with the purpose of developing the ability to communicate and represent mathematical ideas. It also provides the opportunity to learn about a useful didactic resource in the teaching and learning of mathematics.